2012
DOI: 10.1111/j.1600-0501.2012.02524.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term evaluation ofAstraTech andBrånemark implants in patients treated with full‐arch bridges. Results after 12–15 years

Abstract: Treatment with Astra Tech TiOblast implants and Brånemark turned implants supporting full-arch bridges showed generally good clinical results with low numbers of implants with marginal bone loss indicative of peri-implantitis. No significant differences were found between the implant systems after 12-15 years in function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(118 citation statements)
references
References 35 publications
9
101
1
3
Order By: Relevance
“…After evaluating each article, 23 studies published between the years 1999 and 2014 were selected. 3,6,[24][25][26][27][28][29][30][31][32]34,[36][37][38][39][40][43][44][45][46][47][48] The most frequent reason for exclusion was a follow-up period of less than 10 years. Of the potential studies for inclusion (n = 59), 36 were excluded after careful analysis.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After evaluating each article, 23 studies published between the years 1999 and 2014 were selected. 3,6,[24][25][26][27][28][29][30][31][32]34,[36][37][38][39][40][43][44][45][46][47][48] The most frequent reason for exclusion was a follow-up period of less than 10 years. Of the potential studies for inclusion (n = 59), 36 were excluded after careful analysis.…”
Section: Search Resultsmentioning
confidence: 99%
“…Two studies did not relate the number of drop-outs. 3,44 In 19 studies, 3,6,[24][25][26][27][30][31][32]34,[36][37][38][39][40]43,45,47,48 the implants were placed in healed sockets using the standard surgical protocol, in accordance with the principles described by Brånemark et al 49 In two studies, 28,29 immediate implants were placed with immediate prosthetic loading as well. In two studies, 44,46 the implants were placed in healed sockets, however there was early prosthetic loading.…”
Section: Studies Includedmentioning
confidence: 99%
“…Dental implants have been used with great success in most patients, with a survival rate of 95% over a 10-year period (Adell et al 1981;Rasmusson et al 2005;Ravald et al 2013). However, studies have shown biological complications such as peri-implant mucositis and peri-implantitis with a high prevalence (Zitzmann & Berglundh 2008;Koldsland et al 2010;MirMari et al 2012).…”
mentioning
confidence: 99%
“…Osseointegration has been observed only after loading. [21][22][23][24] Therefore, future studies should be performed to assess the effects of these medications on the load-bearing ability of the interface, associated with micromotions applied transcutaneously to the implants during bone repair. Similar studies have been performed previously by Wazen et al 25 Currently, there are no reports in the literature showing statistically significant differences among osteoporotic patients rehabilitated with dental implants.…”
Section: Discussionmentioning
confidence: 99%